2D-black phosphorus/polyaniline hybrids for efficient supercapacitor and hydrogen evolution reaction applications. Issue 18 (24th August 2022) - K., Namsheer; Kapse, Samadhan; Manoj, Mridula; Thapa, Ranjit; Rout, Chandra Sekhar
Abstract : BP/polyaniline hybrid is considered as a promising candidate for energy storage/conversion due to their interesting features compared to existing materials. Abstract : With the emergence of wearable and portable electronics, solid-state supercapacitors are considered as a promising candidate to power electronic devices because of their interesting features compared to existing energy storage devices. Polyaniline is a promising candidate for energy storage and conversion applications due to its high theoretical capacitance and intrinsic conductivity. Still, relatively sluggish rate capability and energy storage performance should be addressed to compete with existing high-performance electrode materials. Here, we fabricated a solid-state supercapacitor electrode with an organic-inorganic hybrids of polyaniline (PANI) and black phosphorus (BP) to overcome the sluggish electrochemical performance. The fabricated supercapacitor device provides an exceptional specific capacitance of 350 mF cm −2 (116 F g −1 ) at a current density of 0.4 mA cm −2 and displays a high energy density of 31.1 μW h cm −2 at a power density of 330 mW cm −2 along with good cycling stability of 83.3% after 10 000 charge–discharge cycles. Also, this material shows a decent electrocatalytic HER performance with an overpotential value of 128 mV at a current density of 10 mA cm −2, a Tafel slope of 71 mV dec −1, and outstanding stability up to 24 h. Finally, DFT studies confirmed that the PANI/BP hybrid is a more promising electrode material for supercapacitor applications with higher C Q due to a larger density of states near the Fermi level as compared to pristine BP and PANI.